Racial and Ethnic Disparities in Incidence and Prognosis of Perioperative Stroke Among Pediatric Cardiac Transplant Recipients - Laura L. Lehman; Elizabeth Mostofsky; Soziema Salia; Suruchi Gupta; Francisco J. Barrera; Lathan Liou; Murray A. Mittleman (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background In the general population, Black children have a higher incidence of stroke and all‐cause mortality after stroke than White children. Beginning 6 months following cardiac transplantation, Black children have higher mortality than White children. However, whether there are racial and ethnic disparities in incidence and all‐cause mortality following perioperative stroke among pediatric cardiac transplant recipients is unknown. Methods and Results Using the Scientific Registry of Transplant Recipients, we studied children who underwent their first heart transplant in the United States between January 1994 and September 2019. Using multivariable logistic regression, we assessed the association between race and ethnicity and perioperative stroke. We used multivariable piecewise Cox regression to examine the association between race and ethnicity and mortality among survivors of perioperative stroke. Among 8224 children who had a first cardiac transplant, 255 (3%) had a perioperative stroke. Black children had 32% lower odds of perioperative stroke compared with White children (adjusted odds ratio, 0.68 [95% CI, 0.46–0.996]). Following perioperative stroke, mortality rates were similar for Black and White children in the first 6 months (adjusted hazard ratio [HR], 0.99 [95% CI, 0.44–2.26]). However, Black children had a higher mortality rate than White children beyond 6 months (adjusted HR, 3.36 [95% CI, 1.22–9.22]). Conclusions Among pediatric cardiac transplant recipients, Black children have a lower incidence of perioperative stroke than White children. Among survivors of perioperative stroke, mortality is initially similar by race and ethnicity, but beyond 6 months, Black children have over a 3‐fold higher mortality rate than White children. Identifying and intervening on potential differences in care is essential to addressing these disparities.